KAJIAN TAMPILAN FISIK, CITRA MEREK DAN PEMASAR DARI MULUT KE MULUT TERHADAP KEPUTUSAN PEMBELIAN PADA SALON NOONA BEAUTY KOREA KOTA BARABAI KABUPATEN HULU SUNGAI TENGAH - Cici Asmawati; Riky Welli Saputra (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2021)
The purpose of this study was to analyze the physical appearance, brand image and marketer's word of mouth either partially or simultaneously influence the purchasing decision at Noona Beauty Korea salon in Barabai, Hulu Sungai Tengah Regency.The population in this study were all customers or consumers of the Noona Beuty Korea salon in Barabai, Hulu Sungai Tengah Regency. The number of samples is 100 respondents. The sampling technique in this study used a random sampling technique, or random sampling. The data in this research were obtained directly from interviews by distributing questionnaires. The analytical tool used is the research instrument test, classical assumption test, multiple linear regression, t test, F test and R2 testThe results showed that there was an effect of Physical Appearance on Purchase Decisions at Noona Beauty Salon Korea Barabai, Hulu Sungai Tengah Regency. There is an influence of Brand Image on Purchase Decision at Salon Noona Beauty Korea Barabai, Hulu Sungai Tengah Regency. There is the influence of marketers by word of mouth on purchasing decisions at Noona Beauty Salon Korea Barabai, Hulu Sungai Tengah Regency. There is a joint influence between the variables of Physical Appearance, Brand Image, and Word of mouth Marketers on Purchase Decisions at Noona Beauty Salon Korea Barabai, Hulu Sungai Tengah Regency.